New records of a rare species Nitella capillaris (Krock.) J.Groves et Bull.-Webst. (Charophyta, Charales) in Ukraine - Borysova, O.V.; Gromakova, A.B.; Burova, O.V. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2025)
The data of new records of Nitella capillaris are presented. This rare Holarctic species was found in May 2025 in Mozh River (right tributary of the Siverskiy Donets River) and in temporal waterbody of its floodplain in Chuhuiv District (Kharkiv Region, Ukraine) within Forest-Steppe zone. A description of morphological characters, information on general distribution, ecology, and sozological status of the species are provided.